Luteal phase estradiol versus luteal phase GnRH antagonist administration: their effects on antral follicular size coordination and basal hormonal levels - Batool Rashidi; Roya Nasiri; Haleh Rahmanpour; Ensieh Shahrokh Tehraninejad; Maryam Deldar (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2011)
Background: The differential efficacy between long GnRH agonist with antagonist can partly be due to the preexisting differences in the early antral follicles before ovarian stimulation.Objective: To compare the effect of pretreatment by estradiol with GnRH antagonist on antral follicular size coordination and basal hormone levels in GNRH antagonist protocol.Materials and Methods: On cycle day 3 (control/day 3), women underwent measurements of early antral follicles by ultrasound and serum FSH and ovarian hormones then were randomized to receive oral estradiol 4mg/day (n=15) or 3mg cetrorelix acetate (n=15) in luteal phase before subsequent antagonist protocol. Participants were re-evaluated as on control/day 3.Results: There was a significant reduction of mean follicular sizes in each group after medical intervention (7.63±2.11 Vs. 4.30±0.92 in group A and 8.73±1.96 Vs. 4.13±1.11 in group B) (p=0.0001). The magnitude of follicular size reduction was significantly higher in group B (-4.60±2.04 Vs. -3.33±2.28) (0.027). There was a non significant attenuation of follicular size discrepancies in two groups. FSH and inhibin B levels in the day 3 of the next cycle in both groups were significantly decreased but did not have significant difference between two groups.Conclusion: Both luteal E2 and premenstrual GnRH antagonist administration reduces the follicular sizes significantly and GnRH antagonist acts more potently than E2 in this way but attenuation of follicular size discrepancies in both treatment is not significant